Identifikasi Litologi Batuan Pantai Jolosutro, Kabupaten Blitar Menggunakan Landsat 8 Oli (Tirs) - Rifko Cahyo (Jurnal Matematika dan Sains (JMS), 2023)
The lithology of Jolosutro Beach, Blitar Regency, East Java was studied using remote sensing methods. The purpose of this study was to identify the lithology of rocks at Jolosutro Beach, Blitar Regency, East Java. Satellite images are Landsat 8 OLI/TIRS satellite images. The Landsat 8 OLI/TIRS satellite images were then adjusted and combined with RGB. The results of remote sensing data processing showed that the surface lithology of the study area was dominated by andesite-basalt-wash rocks, whose origin is suspected to be from Futhokria and Tenggeri mountains.